Stars and stardom in Brazilian cinema - Bergfelder, Tim; Shaw, Lisa, 1966-; Vieira, João Luiz (New York : Berghahn Books, 2017)
Despite the recent explosion of scholarly interest in "star studies," Brazilian film has received comparatively little attention. As this volume demonstrates, however, the richness of Brazilian stardom extends well beyond the ubiquitous Carmen Miranda. Among the studies assembled here are fascinating explorations of figures such as Eliane Lage (the star attraction of Sao Paulo's Vera Cruz studios), cult horror movie auteur Coffin Joe, and Lazaro Ramos, the most visible Afro-Brazilian actor today. At the same time, contributors interrogate the inner workings of the star system in Brazil, from the pioneering efforts of silent-era actresses to the recent advent of the non-professional movie star.
Introduction / Lisa Shaw and Tim Bergfelder -- Consuming visions: female stars, the melindrosa and desires for a Brazilian film industry / Maite Conde -- A star system created by fans: Pernambucan cinema in the 1920s / Luciana Correa de Araujo -- A star in the spotlight: Carmen Santos and Brazilian cinema of the 1920s / Ana Pessoa -- Carmen Miranda: from national star to global brand / Ana Rita Mendonca and Lisa Shaw -- Cinelandia magazine and the creation of home-grown movie stars in the 1950s / Lisa Shaw -- Oscarito and Grande Otelo: 'the terrible twosome' / João Luiz Vieira and Leonardo Macario -- Eliane Lage: a falling star in the skies of the Tropics -- Ana Carolina de Moura Delfim Maciel -- Radio stars on screen: critiques of stardom in Moacyr Fenelon's Tudo azul (1952) / Luis Alberto Rocha Melo -- Jece Valadao, the 'charming crook': a star image between tradition and modernity / Rafael de Luna Freire -- Jose Mojica Marins versus Coffin Joe: auteurism and stardom in Brazilian cinema / Laura Canepa -- As loiras: Brazil's screen blondes / Stephanie Dennison -- a star is born: the rising profile of the non-professional actor in recent Brazilian cinema / Charlotte Gleghorn -- The black body reframed: Lazaro Ramos and the performance of interracial love / Ben Hoff -- Seu Jorge as a cross-media star: from local authenticity to global appeal / Katia Augusta Maciel -- Latin lover or Latin(o) loser? Rodrigo Santoro and the Hollywood stereotype / -- Daniel O'Brien.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Motion picture actors and actresses -- Brazil; Motion pictures -- Brazil -- History and criticism; Cinéma -- Brésil -- Histoire et critique; PERFORMING ARTS -- Reference; ART / Film & Video; Motion picture actors and actresses; Motion pictures; Brazil; Criticism, interpretation, etc